Tax system and its role in government regulation - Taniev A.B. (International Journal on Orange Technologies, 2020)
This article examines the issues of state regulation with the help of taxes, proposes a new classification of tax literature, and analyzes the problems and their solutions in the tax system. Together with these, we propose legislative regulation of tax control in order to improve tax system.